Stab Injury of the Thoracic Aorta: Computed Tomography Findings - Seyma Yildiz; Huseyin Toprak; Asli Serter; Ercan Kocakoç (Case Reports in Radiology)
Stab injury of the thoracic aorta is a rare condition with high mortality rate. Patients must be evaluated carefully, and the diagnosis usually should be confirmed by radiological modalities. In this case, we report a 37-year-old man presented with a penetrating stab injury to the upper back and the thoracic aorta, and the diagnostic role of computed tomography is discussed.